2020
DOI: 10.1016/j.plantsci.2019.110281
|View full text |Cite
|
Sign up to set email alerts
|

Remote sensing techniques and stable isotopes as phenotyping tools to assess wheat yield performance: Effects of growing temperature and vernalization

Abstract: Araus JL, Remote sensing techniques and stable isotopes as phenotyping tools to assess wheat yield performance: effects of growing temperature and vernalization,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 78 publications
1
10
0
Order By: Relevance
“…These results are also supported by the phenotypic correlations between the 108 individual plots. Negative correlations of the GGA and NDVI measured at anthesis with GY have been reported previously in wheat under Mediterranean conditions ( Rezzouk et al, 2020 ). The relationships of GGA assessed earlier during the crop cycle (at tillering) to GY were positive.…”
Section: Discussionsupporting
confidence: 76%
“…These results are also supported by the phenotypic correlations between the 108 individual plots. Negative correlations of the GGA and NDVI measured at anthesis with GY have been reported previously in wheat under Mediterranean conditions ( Rezzouk et al, 2020 ). The relationships of GGA assessed earlier during the crop cycle (at tillering) to GY were positive.…”
Section: Discussionsupporting
confidence: 76%
“…Accordingly, a* and u* measurements are also related to 'greenness', where the values go from high negative (green) to low negative or even positive values (lack of green). Furthermore, Rezzouk et al [64] observed that ground-based RGB imagery presented a higher resolution than aerial images, since they found that the number of pixels per plot decreased drastically when acquiring images aerially. In our case, this was probably not the case since the pixel resolution of RGB and UAV multispectral imagery were <1 cm and 5 cm, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, it was-to our knowledge-the first time that these two indices were related to visual breeder scores. In phenotyping studies, H and NDLab previously proved useful for predicting grain yield or for assessing disease severity in wheat and maize [39,[81][82][83]. MGRVI was the best performing RGB index, although the difference with VARI was minimal.…”
Section: Research Question 1: Visual-based Indices Are Good Proxies Fmentioning
confidence: 99%